PROBLEMATIKA DEMOKRASI PRESIDENSIL PASCA PERUBAHAN UNDANG-UNDANG DASAR - Abdul Aziz Zaini; Maturidi Maturidi (Jurnal Studi Ilmu Pemerintahan, 2021)
Abstract After the changes to the Constitution (UUD), Indonesia, which previously adopted a parliamentary system of government, turned into a presidential system of government, which still has many democratic problems. These changes also have implications for changes in the government system, including The President is directly elected by the people through general elections, the Position of the People's Consultative Assembly (MPR) which was previously the highest state institution to be a high state institution, Strengthening the role and authority of the House of Representatives (DPR) in the field of legislation and oversight of the executive. One of the provisions which strongly indicates the strength of the presidential system in the 1945 Constitution is Article 7C, which states that the President cannot freeze and/or dissolve the DPR. Historically, many have argued that this article was raised as a response to the statement of former President Abdurrahman Wahid, who had issued a decree to dissolve the DPR when he served as President of the Republic of Indonesia.